Pengaruh Front Time terhadap Tegangan Residu Arester ZnO 18 kV - Riky Dwi Puriyanto; Avrin Nur Widiastuti (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
Electrical system in Indonesia has two main parts that cannot be separated, the source (provider) and the load (end user). Various attempts have been taken to comply with the load requirement, one of them is by creating a reliable system. The reliability of the system can be achieved by protecting component system from power disturbances, e.g., overvoltage (surge). The characteristic of an surge is hard to define. Overvoltage that travels in the transmission line is affected by the line impedance and may cause an alteration in the characteristics of the resulting waves. One of the alterations that may appear is front time value. This research presents a laboratory testing of an 18 kV Zinc- Oxide (ZnO) arrester with various front time values in the ra ngeof 0-30 μs. The various front time values can affect residual voltage with the average value which is equal to 39972.25 V for input voltage (Vpi) 60 kV and 42150 V for 100 kV. The increment of front time makes the value of residual voltage decrease, but the descent is not significant. The change of front time also can affect the residual voltage waveform as output of 18 kV ZnO arrester.